Evaluation of Sub-National Expenditure in India: A Composite Index Approach - VINEET, (International Journal of Advanced Research and Multidisciplinary Trends (IJARMT), 2025)
The proposed Composite Index comprises of ten Minor Fiscal Indicators that make an empirical analysis of the fiscal health of states. The major Indices of the study are Debt Index, Debt Sustainability Index, Revenue Efficiency Index, Expenditure Quality Index, Deficit Index. In this study, 17 states and 2 union territories with legislature namely Delhi and Puducherry are taken into analysis from the time period of 2012 to 2020. The progress of states under the analysis are ranked throughout the time period and shows the consistent retrogression in the Fiscal Performance of the states. Relative Distance method is used in construction of the Index. The paper focuses on articulating the causes of changes in the ranks of states based on the values derived from the composite Fiscal Performance Index (FPI). Major factors that influence the performance of the states were efficiency in allocation of expenditure, increase in revenue generating capacity of the state, decrease in debt stock and simultaneous decrease in fiscal and Revenue Deficit (RD) of the states. The most influential factor was the increase or decrease in the debt sustainability ratio of the state which is measured as DSI. The observation highlights Odisha as the most outstanding performer, consistently securing a position within the top five rankings across all time intervals. The analysis indicates that Punjab, Kerala, Haryana, and West Bengal exhibited the least favourable performances within the studied time period.